(untitled) (Annals of Medical Research, 2022)
Objective: The purpose of this study is to evaluate the activity of daratumumab in combination with polycaprolactone (PCL) nanoparticles (NPs) for decreasing toxicity and enhancing the anticancer efficiency of doxorubicin (Dox) for diffuse large B-cell lymphoma (DLBCL). Material and methods: Polycaprolactone nanoparticles were developed using double emulsion technique. For characterization of blank and doxorubicin loaded PCL nanoparticles; particle size, polydispersity index and surface charge were determined. Cell culture study was realized to conclude the cytotoxicity of DOX-loaded PCL NPs alone or combination with Daratumumab. Results: Blank and Dox-loaded PCL nanoparticles remained within 235 nm and 250 nm, respectively. Zeta potential values were -3.9 and -13.3 mV for blank and Dox-loaded PCL nanoparticles, respectively. In cell culture study, whole formulations showed a time-dependent model; the cytotoxicity enhanced with the increase of incubation time. Blank nanoparticles have no toxicity; cell viability was above 85%. Dox-loaded nanoparticles showed more toxicity to A20 cells than Dox solution. Dox-loaded NPs in combination Daratumumab exhibited higher cell toxicity than Dox-loaded NPs and mAb solution, respectively (P <0.05). Conclusion: Dox-loaded PCL nanoparticles in combination with antibody-targeted chemotherapy could be a considered as promising synergistic strategy for controlling tumor growth by increasing the antitumor efficacy while minimizing toxicity.